Analysis of body mass index in children with polyarticular hypermobility - Paulina Lebowska; Magdalena Gębska (Kazimierz Wielki University, 2018)
Admission: Polyarticular hypermobility is joint mobility, defined as increased based on accepted standards. Structural changes resulting from the hypermobility arthritis could lead to significant disorders of the musculo-skeletal and others. Inadequate weight gain in children with joint hypermobility may be an additional factor that will be negatively affected locomotor system. Due to the consequences of hypermobility, it seems expedient to show students and their parents methods of prevention and rehabilitation of disorders in case of the emergence of health risks. Objective: Analysis of the BMI distribution on centile charts of children with polyarticular hypermobility. Material and method: The study was conducted in 100 children aged 6 to 11 years attending primary schools in Szczecin. In children made anthropometric measurements (height, weight, etc.) on the basis of which calculated the body mass index (BMI) and this values assigned to the corresponding centile charts sex and age. In order to determine the occurrence of joint hypermobility in children was carried out Modified Beighton Scale. Children with a positive test result in Beighton Scale constituted study group (Group I). The control group (Group II) included in a random fashion an equal number of boys and girls in the same age as the Group I in which the rated value of the BMI, and there were no joint hypermobility. Results: In the group of 100 children, hypermobility of joints in Beighton Scale stawierdzono in 34% of the respondents (41,93% girls, 30,43% boys). Statistical evaluation BMI on the centile charts between the Group I and Group II showed no statistical significance (p = 0,88). Conclusions: Value of BMI on the centile charts are comparable in children with hypermobility and children without occurring features hypermobility of joints. Given the prevalence of frequensy hypermobility among children and young people, prevention in the form of assessment of the hypermobility is very important.